Avaliação do aumento da frequência de ordenhas no início da lactação sobre desempenho produtivo e dinâmica da renovação celular mamária em vacas leiteiras - Juliana Aparecida Mello Lima (2015)
The increased milking frequency (IMF) during early lactation stimulates an increase in milk yield that partially persists through the remainder of lactation. However, the effects of IMF on cellular turnover and udder health have not been clearly established. The objectives of the present study were to evaluate the effects of mammary biopsies on tissue characteristics postbiopsy, udder health and determine the effect of increased milking frequency (IMF) during early lactation on milk yield, composition and somatic cell count (SCC), histomorphometry, proliferation and apoptosis in mammary epithelial cells. Sixteen cows ½ Holstein × Zebu (HxZ) were randomly distributed into two groups. The control group was milked twice a day (2X) throughout the entire lactation, and the group subjected to IMF was milked four times a day (4X) from two to 21 DIM, and twice a day (2X) from 22 to 210 DIM. Mammary biopsies were performed in eight cows from each group on days 2, 7, 14, 21, and 28 postpartum. Qualitative and quantitative analyses of the tissues were conducted by histologic examination. Udder health was assessed daily from calving to 60 DIM with California Mastitis Test (CMT) and by noting alterations in the milk such as blood, milk clots, blood clots, clinical signs of mastitis. Milk composition and SCC were analyzed before and after the biopsies. Milk production was evaluated before biopsy, on the day of biopsy, and after the biopsy. Milk production, composition and SCC were measured daily from 4 to 30 DIM and then each 15 days until 210 d postpartum. An average of 10 fields at 40× magnification was obtained from each sample. There were no evident changes in mammary morphology as result of milking two or four times/d at any of the evaluated time points. Biopsy wounds healed rapidly without infection. Intramammary bleeding and CMT alterations were observed in 96% and 75% of the biopsied mammary quarters, respectively. Clinical mastitis was diagnosed in 12% of the biopsied quarters. Milk production decreased after biopsies done on days 2, 14, and 21, but it returned to pre-biopsy values within two days. Milk composition and SCC were affected transiently. During the first 21 d of lactation, milk yield in the 4X was 2.6 ± 0,2 kg/d higher than the control group (P < 0.05) and after this day maintained milk yield similar to the control group until the end of the lactation (P 0.05). There was no difference in milk yield up to 210 DIM (P < 0.05). In the three periods, there was no difference in the percentage of fat, protein and lactose (P 0.05). During the IMF, milk SCC, yield, fat corrected milk (3.5%) were higher in 4X than 2X (P < 0.05) and there was no difference after this period and up to 210 DIM (P 0.05).The proliferation and apoptosis of epithelium, stroma and total of mammary cells, as well as the proportion of mammary tissue occupied by alveoli, stroma and lumen were not affected by IMF (P 0.05). Changes in milking frequency during early lactation did not alter mammary cell population dynamics.